Reflections on sexual violence: consequences and actions - Rodriguez Narvaez, Vanessa (2022)
Sexual violence is an alarming public health problem that affects Peruvian society. The situation of this problem is reviewed in terms of its characterization, prevalence in the country, and conditions in which this problem is developed. Then the impact of this problem on society in general as well as on mental health. Subsequently, relevant actions to consider in the prevention and elimination of sexual violence are analyzed, understanding that this problem requires a multisectoral intervention, considering socio-cultural, biopsychological, and legal aspects.